Economic behavior of agricultural land market subjects - V. I. Trofimova (Управление)
The purpose of the study is to build the agricultural land market subjects’ economic behavior models. The formation of rational land use in the agrarian sphere indicates influence of institutional factors – motives and interests of land owners that allow to ensure land distribution included in the market turnover between the most efficient users. The structural scheme of the agricultural land market subjects’ behavior motives has been proposed. The motives of sellers in the land market are to optimize income that is achieved by increasing a land plot attractiveness. Buyers are guided by the possession motives, use and disposal of land by acquiring a land plot. Sellers and buyers of land plots are individuals and legal entities. Agricultural organizations, individual entrepreneurs, farms, personal subsidiary plots, and citizens (rural population) participate in land sailing. Buyers in the market are owner, land user, landowner, and tenant. The functions of sellers and buyers have been systematized considering the purpose and action of the actors. Destructive and rational models of the agricultural land market actors’ economic behavior have been presented and developed. The application of the destructive model is associated with negative consequences characterized by land withdrawal from economic turnover, change of its intended purpose, and land transfer to another category. The rational model includes finding an optimal alternative under a set of constraints and provides for a high level of human intelligence and knowledge to make right decisions. Factors of this model are coordination of land ownership institutions and creation of a legal framework. It is characterized by strict administrative and legal regulation that contributes to eradication of shadowing in land relations. The area of application of the developed rational model of the agricultural land market subjects’ economic behavior is scientific organizations, agro-industrial complex management bodies at the regional and municipal levels, and agricultural producers.